1977
DOI: 10.1042/bj1660275
|View full text |Cite
|
Sign up to set email alerts
|

The manipulation of cellular cytochrome and lipid composition in a haem mutant of Saccharomyces cerevisiae

Abstract: 1. The ole-3 mutant of Saccharomyces cerevisiae has an early lesion in the pathway of porphyrin biosynthesis. 2. This results in the loss ofall haem-containing enzymes, including the mitochondrial cytochromes, and prevents the synthesis of components whose formation requires haem-containing enzymes, including unsaturated fatty acids, ergosterol and methionine. 3. The pleiotropic effects of the primary lesion are reversed by growing mutant ole-3 aerobically in the presence of intermediates of the porphyrin-bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…To identify novel binding partners of p-arrestin 2, we used the yeast two-hybrid system based on a GAL4-6-arrestin 2 fusion protein to screen a rat brain cDNA libran (13). Three positive clones were obtained, two of which encoded fusion proteins of the GAL4 activation domain with a COOH-terminal portion of JNK2 and one that encoded a COOH-terminal portion of the JNK3 isoform (14).…”
Section: P-arrestin 2: a Receptor-regulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify novel binding partners of p-arrestin 2, we used the yeast two-hybrid system based on a GAL4-6-arrestin 2 fusion protein to screen a rat brain cDNA libran (13). Three positive clones were obtained, two of which encoded fusion proteins of the GAL4 activation domain with a COOH-terminal portion of JNK2 and one that encoded a COOH-terminal portion of the JNK3 isoform (14).…”
Section: P-arrestin 2: a Receptor-regulatedmentioning
confidence: 99%
“…Deoxidizes the CxxC active site of the PDI letion of COQ5 or HEMI, which blocks biohomolog DsbA, which then catalyzes disulsynthesis of ubiquinone (11,12) or heme fide formation in folding proteins. DsbB is (13), respectively, inhibited respiration and reoxidized by ubiquinone produced during ER-associated cytochromes but did not alter respiration.…”
mentioning
confidence: 91%
“…Hemoproteins are known to participate in several steps of the sterol biosynthetic pathway, including dehydrogenation and demethylation reactions (13,21). Thus, sterol biosynthesis is precluded in anaerobically cultured wild-type cells or in heme-deficient mutants cultured aerobically because of lack of the corresponding hemoproteins (2,3,12). Previous studies have indicated that when wild-type cells are grown aerobically, they are apparently impermeable to exogenous sterols (17,27).…”
mentioning
confidence: 99%
“…Bailey & Parks (1975) showed that zymosteryl esters are not methylated by the Cea methyltransferase in vitro, and its seems likely that the other steryl esters are unavailable for direct biosynthetic modification. Under anaerobic conditions, the steryl esters appear to be converted to the free sterol, of which zymosterol and fecosterol are then completely converted to ergosterol and 24 : 28-dehydroergosterol, but lanosterol remains as such because of the absence of molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…A calibration curve was prepared using bovine serum albumin (Calbiochem, Type V). Dry weights of cells were determined volumetrically by centrifuging a sample of cells in calibrated thick-walled graduated glass capillary tubes (Astin et al, 1977). Ethanol was assayed using the g.1.c.…”
Section: P-hydroxymethylglutarylmentioning
confidence: 99%